The Sandman. Vol. 9, The kindly ones - Gaiman, Neil (DC Comics, 2019)
Morpheus becomes the prey of the Furies--avenging spirits who torment those who spill family blood. A journey both begins and ends for the Lord of Dreams as threads and pieces building since the beginning of the series finally come together in a thrilling climax that forever changes the world of The Sandman.